KEMAMPUAN MENULIS TEKS PERSUASIF DALAM BAHASA BUGIS SISWA KELAS VIII UPT SMP NEGERI 3 LAPPARIAJA KABUPATEN BONE - Musreni, Mila; Syamsudduha, Syamsudduha; M, Asia (Journal Studies in Indonesian Language and Literature, 2025)
This study aimed to describe the ability of Grade VIII students at UPT SMP Negeri 3 Lappariaja, Bone Regency, in writing persuasive texts in Bugis. The population consisted of 45 students from two classes (VIII A and VIII B). Total sampling was employed, and data collection used tests. Results showed that the average score of students' ability in writing persuasive texts in Bugis was 72.76, categorized as proficient. However, based on the criteria that students' ability is considered proficient if 70% or more of the sample students score 70-100, and not proficient if less than 70%, the students' ability in writing persuasive texts in Bugis is considered not proficient. This is because only 26 students (58%) scored 70-100. Therefore, the ability of Grade VIII students at UPT SMP Negeri 3 Lappariaja in writing persuasive texts in Bugis is categorized as not proficient.